Comparison of debris extruded apically and working time used by ProTaper Universal rotary and ProTaper retreatment system during gutta-percha removal (Journal of Applied Oral Science, 2010)
OBJECTIVE: The aim of this study was to evaluate the in vitro action of ProTaper retreatment files and ProTaper Universal in the retreatment of mandibular premolars. MATERIAL AND METHODS: The amount of debris extruded apically was measured and the time to reach the working length and to complete the removal of gutta-percha was observed. Thirty teeth had their canals prepared using ProTaper Universal files and were obturated by the single cone technique. The teeth were then stored at 37ºC in a humid environment for 7 days. During the use of the rotary instruments for root canal filling removal, the apical portions of the teeth were attached to the open end of a resin tube to collect the apically extruded debris. RESULTS: ProTaper Universal files were significantly faster (p=0.0011) than the ProTaper retreatment files to perform gutta-percha removal, but no significant difference was found between the files regarding the time to reach the working length or the amount of apical extrusion. CONCLUSIONS: ProTaper Universal rotary had better results for endodontic retreatment, and both techniques promote similar apical extrusion of debris.